Clinical epidemiological and endoscopic characteristics in carriers of the viral hepatitis C with hemodialysis treatment - Mariblanca González Purón; Jesús Fernández Duharte; Daysi Martén Marén (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: The patients with chronic renal failure in hemodialysis treatment constitute an important risk group to acquire the infection for the viral hepatitis C. Objective: To characterize carriers of the viral hepatitis C in hemodialysis treatment according to clinical epidemiological and endoscopic variables.  Methods: An observational, descriptive, retrospective and longitudinal investigation of 63 patients with chronic renal failure, in hemodialysis treatment, carriers of the viral hepatitis C was carried out, who were assisted in the Gastroenterology Service of Dr. Juan Bruno Zayas Teaching General Hospital in Santiago de Cuba from January, 2015 to September, 2019. Results: In the investigation there was a prevalence of the male sex, the 31-60 age group, besides hypertension and the diabetes mellitus as personal history. The risk factors of more incidence were injections and frequent transfusions. Conclusions: There was a significant correlation between the time in hemodialysis and the time of diagnosis of the viral hepatitis C; however, the viral replication stayed low.